It is true because
when you separate 2y^2 +9y -18, you are supposed to get the factors
(2y-3)(y+6), when you multiply this it gives you the first equation, we know
this because when we multiply the first term it gives us exactly 2y^2 and if we
multiply the last ones it gives you -18, now here is the tricky part, when we
multiply the middle part we get 12y and -3y, when we add these up we get 9y,
now is that the same middle as in the equation? Yes… then our factors are correct
making this true
Hope this helps
Answer:
OGH and TCA
Step-by-step explanation:
that's quite easy...
the congruency criterion is ASA or Angle side Angle.
i.e. a side lying between two Angles.
so we have
GH = FN= CA
now, G=I= C
and H=N=A
it's pretty clear that G-GH-H = C-CA-A
(just to explain)
hence, the answer
Answer:
x = -1/2
Step-by-step explanation:
(x - 4) * 2 = -9
Divide both sides by 2:
x - 4 = - 9 / 2
Add 4 to both sides:
x = - 1 / 2.